THE EFFECT OF DIGITAL ECONOMY WITH DIGITAL LITERACY AS A MODERATING VARIABLE ON INCREASING RUMAH UMKM INCOME IN DESA PERKEBUNAN TANJUNG KASAU, BATUBARA - Satria Lubis, Andrew; Amalia, Alfi (Proceeding International Seminar of Islamic Studies, 2023)
Rumah UMKM are one of the drivers of development and economic growth in Indonesia. This study aims to examine the effect of the digital economy on Rumah UMKM income in Desa Perkebunan Tanjung Kasau, Batubara with digital literacy as a moderator variable. In this study using a descriptive quantitative method with the sample used are Rumah UMKM actors who are registered as members at the Rumah UMKM in Desa Perkebunan Tanjung Kasau, Batubara and use internet media in their business activities both in promotional activities or transactions. The number of samples as respondents from this study amounted to 300 respondents. The analytical tool used was Smart PLS version 3.0. The results of this study prove that the digital economy has a positive and significant effect on the income Rumah UMKM Desa Perkebunan Tanjung Kasau, Batubara. And the role of digital literacy is significant in moderating the relationship between the two variables. So that there is an indication that Rumah UMKM income will increase if digital literacy is maximized.